A Netnographic Study: Construction of AI-Based Learning Media Training on pintar.kemenag.go.id - Pranajaya, Syatria Adymas; Cahyadi, Ani; Nasir, Muhammad; Riwanda, Agus; Pratama, Dinar (ISLAMIC PEDAGOGY: Journal of Islamic Education, 2024)
This research was conducted to find out how the construction carried out by community participants of Artificial Intelligence (AI)-based Learning Media Training on the pintar.kemenag.go.id application or website facilitated by Badan Litbang dan Diklat Kementerian Agama RI as a virtual training medium. Using the netnography method, researchers try to reveal and analyze the way community participants present the "digital-self". Netnography describes how experience and learning are carried out virtually through the "repetition of experience" that occurs among members/participants in online communities. The AI-based Learning Media Training is constructed as a free and flexible community virtual training. This virtual training is designed to help the general public who are highly motivated to join the training. Training without physical contact and new media influence the construction of a virtual training. The construction can be seen through 3 aspects, namely: internalization, objectivation, and externalization. This research can be concluded to be very liked and considered very helpful in contemporary and useful training, analyzed from the number of comments and reviews of 4,503 and likes through the 4.9 stars icon with details of the number of 5 stars = 4,221; 4 stars = 244; 3 stars = 24; 2 stars = 2; and 1 star = 12 given by participants to the information or material published. The overall score for this training is 94% which is categorized as excellent.